2017
DOI: 10.4103/ija.ija_247_17
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and upper airway measurements: A study in South Indian population

Abstract: Background and Aims:Most studies on upper airway are conducted based on airway measurements in the western population. We set out to find the normal values of upper airway measurements in South Indian population. The aim of this study was to perform various upper airway examinations and to set standards for normal measurements in the South Indian population as well as to analyse the data for predictors of difficult intubation.Methods:This prospective observational study was conducted in a tertiary cancer hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 31 publications
1
25
2
Order By: Relevance
“…[31314] In our study, RHTMD has higher sensitivity and accuracy, better specificity, and highest NPV. The sensitivity of RHTMD in our study was 62.5%, which was comparable with earlier studies,[14151617] but lower compared with some other studies, which could be due to lower cutoff value adopted. [4] The specificity of RHTMD was comparable with earlier reports.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[31314] In our study, RHTMD has higher sensitivity and accuracy, better specificity, and highest NPV. The sensitivity of RHTMD in our study was 62.5%, which was comparable with earlier studies,[14151617] but lower compared with some other studies, which could be due to lower cutoff value adopted. [4] The specificity of RHTMD was comparable with earlier reports.…”
Section: Discussionsupporting
confidence: 85%
“…[310] A recent study in south Indian population, attempted to find out the optimum airway measurements to predict difficult intubation, has reported a cutoff value of 17.1. [17] This is probably due to the higher mean TMD (9.03 cm) reported in the study. Though their sample size was good, the study could not provide optimum measurements for the predictive tests, as their best outcome being an area under ROC curve of 0.64 for RHTMD and all other indices giving a value <0.50.…”
Section: Discussionmentioning
confidence: 77%
“…[9] In one of the studies done by Krishna et al (2005) which was done in Indian population, cut-off value was 21.3 cm. [15] Balakrishnan and Chockalingam (2017) in their study concluded a cut-off value of 17.1, [16] which was lower than our study population and in other Indian studies. [15,17,18] Probably, their study had predominantly female population and used TMD cut-off at (9.03 ± 1.2), which was 6.5 in our population.…”
Section: Discussioncontrasting
confidence: 57%
“…Future studies should try and define ethnicity-specific cutoffs and validate them as there are variations in craniofacial features and body habitus across different races. [ 21 22 ] TMHT data on caucasian population is lacking. The ideal way of measuring the airway parameters should be defined and pilot testing for interobserver variablity should be strongly encouraged before embarking clinical evaluation.…”
Section: Discussionmentioning
confidence: 99%